2018
DOI: 10.1007/978-3-319-77398-8_3
|View full text |Cite
|
Sign up to set email alerts
|

Tuning EASY-Backfilling Queues

Abstract: Abstract. EASY-Backfilling is a popular scheduling heuristic for allocating jobs in large scale High Performance Computing platforms. While its aggressive reservation mechanism is fast and prevents job starvation, it does not try to optimize any scheduling objective per se. We consider in this work the problem of tuning EASY using queue reordering policies. More precisely, we propose to tune the reordering using a simulationbased methodology. For a given system, we choose the policy in order to minimize the av… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2
1

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 28 publications
(34 reference statements)
2
12
0
Order By: Relevance
“…However, such jobs are expected to be very few. This explains some results found by Lelong et al [21], in which they state that the SQF policy did not lead to many backfilling decisions in their experiments.…”
Section: Backfilling Influencesupporting
confidence: 61%
“…However, such jobs are expected to be very few. This explains some results found by Lelong et al [21], in which they state that the SQF policy did not lead to many backfilling decisions in their experiments.…”
Section: Backfilling Influencesupporting
confidence: 61%
“…All the comparisons and the techniques in the remainder of this paper are applied to the primary queue and the backfilling policy to fixed to SPF. We chose this setting because in [2], Lelong et al showed that reordering the primary queue is more beneficial than simply reordering the backfilling queue and in [6], The authors showed that SPF is a good policy for backfilling.…”
Section: B Scheduling Heuristic: Easy-backfillingmentioning
confidence: 99%
“…However, these works do not address dependencies between the workload and the objectives [10]. The dynP scheduler [2] offers an online approach to tune EASY queue. dynP requires the full simulated schedule for each of the candidate policies in every scheduling step, which makes the scheduling cost much higher than simple EASY.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…However, any customization to the simulator needs to be done at the source code level, which can be complicated and error-prone. PYSS [23,21,28] and OCS [15] have similar characteristics to Alea, but provide less advanced WMS features as they are developed primarily for a specific research work in dispatching. In general, simple simulators like PYSS and OCS hinder the design of novel advanced dispatchers and their evaluation which requires a more flexible way to represent a WMS.…”
Section: Related Workmentioning
confidence: 99%